2019
DOI: 10.1111/sji.12792
|View full text |Cite
|
Sign up to set email alerts
|

CD21−/low B cells associate with joint damage in rheumatoid arthritis patients

Abstract: Depletion of B cells is beneficial in rheumatoid arthritis (RA) patients with autoantibodies to citrullinated proteins (ACPA) and/or the Fc portion of immunoglobulins (rheumatoid factor [RF]), suggesting a role for B cells in disease pathogenesis. To date, however, the identity of specifically pathogenic B cell subsets has not been discovered. One candidate population is identified by the low expression or absence of complement receptor 2 (CD21 −/low B cells). In this study, we sought to determine whether ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 54 publications
5
48
0
Order By: Relevance
“…Besides B cell depletion, rituximab induced a depletion of CD4 + T cells in patients with RA, which was associated with clinical response [45]. Studies on peripheral lymphocyte subsets in rheumatic diseases such as rheumatoid arthritis, Sjögren's syndrome, SLE and spondylarthritis have identified changes both within the T and B cells and in some cases associated those changes with disease activity or with phenotypic variations [46][47][48][49][50][51]. Overall, B and T cell subset abnormalities within rheumatic diseases, their association with disease activity or particular disease subgroups and/or anti-inflammatory drugs remain to be better elucidated in larger longitudinal cohorts including in the treatment of naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides B cell depletion, rituximab induced a depletion of CD4 + T cells in patients with RA, which was associated with clinical response [45]. Studies on peripheral lymphocyte subsets in rheumatic diseases such as rheumatoid arthritis, Sjögren's syndrome, SLE and spondylarthritis have identified changes both within the T and B cells and in some cases associated those changes with disease activity or with phenotypic variations [46][47][48][49][50][51]. Overall, B and T cell subset abnormalities within rheumatic diseases, their association with disease activity or particular disease subgroups and/or anti-inflammatory drugs remain to be better elucidated in larger longitudinal cohorts including in the treatment of naïve patients.…”
Section: Discussionmentioning
confidence: 99%
“…Infiltration of inflammatory cells is a pathologic feature of RA, in addition to the hyperplasia of synovial membranes and pannus growth. RA has been investigated for over a century and many studies have indicated that various types of immune cells such as CD4 + Th cells (CD4 + T cells, Th cells), macrophages, and B cells are responsible for the pathogenesis of RA . However, the immunologic mechanism of RA is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…An expansion of a small subset of CD38 low CD21 low B cells in patients with GATA2 deficiency was described 14 . This subset is also expanded in the peripheral blood of patients with systemic lupus erythematosus (SLE) 25 , seropositive rheumatoid arthritis (RA) 26 , and Sjögren's syndrome 27 . Further, in patients with RA, CD21 low B cells were identified as a major B cell population in synovial fluid 28 .…”
Section: Discussionmentioning
confidence: 99%